A Sweat-based Wearable Enabling Technology for Real-time Monitoring of IL-1β and CRP as Potential Markers for Inflammatory Bowel Disease. Issue 10 (28th July 2020) - Jagannath, Badrinath; Lin, Kai-Chun; Pali, Madhavi; Sankhala, Devang; Muthukumar, Sriram; Prasad, Shalini
Abstract: Background: More than 1.2 million people in the United States are affected by inflammatory bowel disease (IBD). Inflammatory bowel disease has a natural course characterized by alternating periods of remission and relapse. Currently, disease flares are unpredictable as they occur in a random way. Further, current testing methods and practices lack the ability for real-time tracking of flares. There exists no technology that can be utilized for continuous monitoring of biomarkers, as most of these rely on samples such as blood, feces, and testing methods by which continuous monitoring is not feasible. Cytokines play a key role in IBD; the development, recurrence, and exacerbation of the inflammatory process are orchestrated by their levels in time and space. Cytokines are also present in sweat. We hypothesize that demonstrating real-time continuous monitoring of interleukin-1β (IL-1β) and C-reactive protein (CRP) may help create an enabling technology to track inflammation in IBD patients and identify flare-ups and assess efficacy of therapy. Methods: A multiplexed SWEATSENSER was used for noninvasive continuous monitoring of interleukin-1β and C-reactive protein in human eccrine sweat. Impedance spectroscopy was used to measure the sensor response. Sweat was collected using an FDA-approved PharmChek patch from 26 healthy human subjects to determine the levels of the 2 study inflammatory markers. Correlation analysis was performed for preclinical validation of the SWEATSENSER with ELISA as the reference method. On-body continuous monitoring measurements were performed on 20 human subjects using EnLiSense's SWEATSENSER wearable device for real-time monitoring studies. Results: The sensor device can detect interleukin-1β and C-reactive protein in sweat over a dynamic range of 3 log orders. Pearson correlation of r = 0.99 and r = 0.95 was achieved for IL-1β and CRP, respectively, for the SWEATSENSER with ELISA. Bland-Altman results further confirmed a good agreement (mean bias of –0.25 and –3.9 pg/mL for IL-1β and CRP, respectively) of the device with the reference method, demonstrating applicability of the device for real-time monitoring. Continuous on-body measurements were performed in 20 healthy human subjects for the detection of IL-1β to establish the preclinical utility of the sensor device. The continuous on-body measurements in healthy cohort reported a mean IL-1β concentration of 28 pg/mL. Stable measurements for over continuous 30 hours was reported by the device. Conclusion: This work demonstrates the first proof-of-feasibility of multiplexed cytokine and inflammatory marker detection in passively expressed eccrine sweat in a wearable form-factor that can be utilized toward better management of inflammatory bowel disease. This is a first step toward demonstrating a noninvasive enabling technology that can enable baseline tracking of an inflammatory response. Furthermore, this is the first study to report and quantify the presence of CRP in human eccrine sweat. Graphical Abstract: Abstract : This work is the first demonstration of an enabling technology to continuously and noninvasively monitor cytokine inflammatory markers from passive human eccrine sweat that are hypothesized to be upregulated due to the host response to the disease, which may help in identifying flare-ups for better management in IBD patients.